Surface modified malaysian Ceiba Pentandra (L.) Gaertn. as natural oil adsorbent - Mat Noh, Ahmad Zakwan (2018)
The risk of oil spills escalate as the petroleum industry growing and the toxic hydrocarbons released to the environment are harmful to both animals and living things. Producing a cost-efficient and environmental-friendly sorbent are fundamentals. Sorbent must not leave traces of harmful chemicals which may later on affect the nature. Adsorption technique by using kapok fiber has been proven to be the most promising method compared to the other oil-containment approaches. Kapok have an excellent hydrophobic-oleophilic structure. In this study, four-hour esterification of fatty acids (oleic acid and decanoic acid) at 50˚C±5˚C modified the surface characteristics of the kapok fiber to investigate the effects on the oil sorption and dynamic oil retention capacity using the standard F726-99 (ASTM, 1998c). This research focused on analyzing the sorption capacity of raw kapok and its modified versions in accordance to the variation of oil viscosity (diesel, engine oil, and light crude oil). In addition, the experimental results were compared with adsorption isotherms models which are Langmuir and Freundlich to identify the sorption behavior of the adsorbent. Raw, oleic grafted, and decanoic grafted kapok show high sorption intake for crude oil; 66.50g/g, 73.22g/g, and 79.27g/g respectively. Raw kapok shows highest sorption for diesel (50.41g/g) and engine oil (60.32g/g). However, the modified versions of kapok show better dynamic retention capacity compared to the raw kapok. Malaysian raw kapok and the modified versions all follows the Langmuir isotherm model.